The multilingual muse : transcultural poetics in the Burgundian Netherlands - Armstrong, Adrian; Strietman, Elsa (Legenda, Modern Humanities Research Association, 2017)
In the late Middle Ages, the Low Countries — ruled by the Dukes of Burgundy and their Hapsburg successors — boasted a dynamic literary culture in both French and Dutch. Speakers of these languages interacted in more ways than might be expected. Writers shared topics and techniques; works were translated; printers who spoke one language published material in the other. The Multilingual Muse brings together an unprecedented community of scholars, both historians and literary specialists, to chart these interactions. It reveals that poetry, far from resisting linguistic and cultural translation as is widely supposed, was a deeply transcultural enterprise in the region.